Regional Spillover Effect Terhadap Pertumbuhan Ekonomi Kota Pekanbaru - M. Irfan Rosyadi; Sinta Yulyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The spillover effect of economic activity from one area to another is due to the inter-sector linkages, which have implications for economic growth. This study examines and presents empirical evidence on the effects of economic growth in the districts of Siak, Pelalawan, Kampar, Kuantan singingi, and Bengkalis, which have spatial impacts on the economic growth of Pekanbaru City. Through quantitative methods with secondary data from the Regency / City Central Statistics Agency in Riau Province, the data used is the Gross Regional Domestic Product from 2010 to 2019, then analyzed using the Multiple regression method. The study results show that Kampar, Kuantan singingi, Pelalawan, and Siak districts have a significant effect on the economic growth of Pekanbaru City, while Bengkalis does not affect. Not all of the natural resources owned by each district can provide a spillover effect of growth. However, a dominant sector in absorbing labor will provide a spillover effect of economic growth from one region to another. Keyword: Regional Spillover Effect. Economic Growht, Multiple Regression. Pekanbaru